2017
DOI: 10.1016/j.ejrad.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced radiation damage caused by iodinated contrast agents during CT examination

Abstract: The iodinated contrast agent itself can lead to an increase in the level of DSBs as assessed with γH2AX foci formation, and the application of ICA can amplify DNA damage induced by diagnostic x-ray procedures such as whole abdominal CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…Many further studies used the γ-H2AX assay both ex vivo and in vivo for investigation of DNA damage in blood lymphocytes induced during CT examinations and, in particular, to investigate the effect of iodinated contrast agents [23,[29][30][31][32][33][34][35][36]. In agreement with the results of our ex vivo study, the majority of these studies report an increase of DNA damage in the contrast media-enhanced samples.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Many further studies used the γ-H2AX assay both ex vivo and in vivo for investigation of DNA damage in blood lymphocytes induced during CT examinations and, in particular, to investigate the effect of iodinated contrast agents [23,[29][30][31][32][33][34][35][36]. In agreement with the results of our ex vivo study, the majority of these studies report an increase of DNA damage in the contrast media-enhanced samples.…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with the results of our ex vivo study, the majority of these studies report an increase of DNA damage in the contrast media-enhanced samples. Despite the findings in some of the ex vivo studies that this increase is only significant for high concentrations of the iodinated contrast agents used (up to 50 mg mL −1 ) or high radiation doses (up to 1 Gy) but not in a range that is clinically relevant for diagnostic procedures [30,34], many patient studies show that there is an 30 to 107% increase in DNA damage when contrast agents are applied compared to non-contrast enhanced examinations [31,32,[34][35][36].…”
Section: Discussionmentioning
confidence: 98%
“…The results showed that the mean percentage increase (standard deviation) in the estimated organ dose varied across organs and was 26.3%  4.3 in lungs (the largest organ of interest in the procedure) (6). A similar investigation by Wang et al (5) showed that there was a 37.9% increase in the number of foci per cell in patients undergoing iodinated contrast-enhanced CT urography compared to patients who underwent nonenhanced abdominal CT. These effects are of the same order of magnitude.…”
mentioning
confidence: 68%
“…It should be acknowledged that the estimates above do not exactly quantify the same influence; the measurements of foci per cell in the studies by Piechowiak et al (4) and Wang et al (5) were obtained in peripheral blood lymphocytes and not in organ tissues. Moreover, although the number of foci per cell is a surrogate of DSBs, the link between DSBs and subsequent cancer risk is not yet well established (7).…”
mentioning
confidence: 97%
“…It should be acknowledged that the estimates above do not exactly quantify the same influence; the measurements of foci per cell in the studies by Piechowiak et al (4) and Wang et al (5) were obtained in peripheral blood lymphocytes and not in organ tissues. Moreover, although the number of foci per cell is a surrogate of DSBs, the link between DSBs and subsequent cancer risk is not yet well established (7).…”
mentioning
confidence: 97%